Strategi Pengelolaan Kelas Dalam Upaya Meningkatkan Keaktifan Belajar Peserta Didik - Aprilia, Gita; Sianturi, Kristina Agnes; Kuswandari, Erika Aryani; Fikriansyah, Muhamad Irgi; Mustikaati, Wina (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This research examines classroom management strategies to increase student learning engagement. Classroom management is an essential skill that educators must master to create a conducive and productive learning environment. Through a qualitative literature review method, this research analyzes various relevant literature on the concepts of classroom management, student learning engagement, common problems in classroom management, and effective strategies that can be implemented. The results show that effective classroom management includes building positive relationships with students, using interactive questioning techniques, implementing cooperative learning, establishing clear rules, providing positive feedback, and using various teaching methods. The implementation of these strategies has been proven to increase student learning engagement as indicated by increased participation, motivation, and academic achievement. This research concludes that good classroom management is not only the responsibility of teachers but also requires collaboration from various parties, including schools and parents of students.